Relationship between inflammatory markers, metabolic and anthropometric variables in the Caribbean type 2 diabetic patients with and without microvascular complications - Roberts Lesley; Nayak B Shivananda (Journal of Inflammation, 2006)
Abstract Background Serum sialic acid and C reactive protein are the markers for inflammation. The main objective of this study was to determine the sialic acid level in Caribbean type 2 diabetic patients with and without microvascular complications and its relationship with metabolic and anthropometric variables. Research design and methods The Caribbean subjects aged 15–60 years with type 2 diabetes were recruited for the study. Fasting venous blood samples were collected from 162 subjects of which 44 were healthy individuals, 44 were of type 2 diabetes, 44 were of type 2 diabetes with nephropathy and 30 were of diabetes with retinopathy. Simultaneously urine samples were also collected from each of the subjects. All the blood samples were processed for lipid profile, glucose, HbA1C, C-reactive protein and sialic acid. The urine samples were analysed for sialic acid and microalbumin. Results Serum sialic acid concentrations were significantly higher among diabetic subjects (66.0 ± 11.7 mg %) as compared to controls (55.2 ± 8.3 mg %). There was a significantly increasing trend of serum sialic acid with severity of nephropathy (71.6 ± 23.6 mg %) and degree of urinary albumin excretion (794.3 ± 805.9). The diabetic retinopathy patients also demonstrated significantly higher values of serum sialic acid (77.9 ± 29.0) and urine microalbumin (351.1 ± 559.9). Elevated serum sialic acid microalbumin concentrations were associated with cardiovascular risk factors such as hypertension, increased waist to hip ratios. (P < 0.05). Sialic acid had no correlation with CRP or any component of the lipid profile. Conclusion The increased serum sialic acid and microalbumin were strongly related to the presence of microvascular complications like diabetic nephropathy and diabetic retinopathy and cardiovascular risk factors like hypertension and waist to hip ratios in Caribbean type-2 diabetic patients. The serum sialic acid may be used as an inflammatory marker and possible indicator of microvascular complications in type-2 diabetic patients.